Sleep disturbances among patients with epilepsy - Staniszewska A (Dove Medical Press, 2017)
Anna Staniszewska,1 Agnieszka Mąka,1 Urszula Religioni,2 Dominik Olejniczak3 1Department of Experimental and Clinical Pharmacology, Medical University of Warsaw, Warsaw, Poland, 2Collegium of Socio-Economics, Warsaw School of Economics, Warsaw, Poland, 3Department of Public Health, Medical University of Warsaw, Warsaw, Poland Aim: The aim of this study was to analyze the prevalence of sleep disorders among patients with epilepsy and to compare the incidence of sleep disorders between the clinical and demographics factors. Materials and methods: The study was conducted among 302 patients with epilepsy. Sleep disturbances were measured with the Polish version of the Pittsburgh Sleep Quality Questionnaire (PSQI). The questionnaire prepared and applied by the authors contained questions relating to sociodemographic characteristics, clinical status, and sleep. Results and conclusion: Mean PSQI score in the study group was 9±2 points, with the range of 4–16 points. PSQI test results were analyzed with regard to clinical and demographic characteristics of those suffering from epilepsy: gender, age, profession, body mass index, illness duration, number of medicines taken, type of seizures, frequency of seizures, time which elapsed since last seizure, provocative factor of seizure attacks, occurrence of adverse effects of antiepileptic drugs (AEDs). Furthermore, the existence of a relationship between PSQI test result and particular sleep-related factors or particular sleep conditions was examined. However, the examination of a relationship between certain independent variables and the final PSQI test result did not prove the existence of a statistically relevant influence (in all cases P>0.05). Keywords: epilepsy, sleep disturbances, sleep, PSQI